2012
DOI: 10.1038/bjc.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer screening participation and impact on melanoma incidence in Germany – an observational study on incidence trends in regions with and without population-based screening

Abstract: Background:The SCREEN (Skin Cancer Research to provide Evidence for Effectiveness of Screening in Northern Germany) project involved population-wide skin cancer screening with whole-body examination by general physicians and dermatologists. It was conducted in the German state of Schleswig-Holstein (July 2003–June 2004), but not in the German state of Saarland.Methods:The population-based registries of Schleswig-Holstein and Saarland provided data on melanoma incidence before, during, and after SCREEN to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 20 publications
7
70
0
8
Order By: Relevance
“…A video clip on sunbed use on YouTube achieved viral dissemination, with 14 million viewings, and was followed by a decrease in the use of indoor tanning beds [40]. Sun prevention campaigns (awareness) and melanoma screening programmes are associated with increased melanoma incidence rates through the detection of prevalent, slow-growing tumours [2,47,48]. Hence, the campaign in Denmark is likely to have contributed to the reported increase in stage I disease by increasing awareness in both the medical community and in the general population, resulting in increased skin self-examination, more physician consultations, and earlier detection.…”
Section: Discussionmentioning
confidence: 98%
“…A video clip on sunbed use on YouTube achieved viral dissemination, with 14 million viewings, and was followed by a decrease in the use of indoor tanning beds [40]. Sun prevention campaigns (awareness) and melanoma screening programmes are associated with increased melanoma incidence rates through the detection of prevalent, slow-growing tumours [2,47,48]. Hence, the campaign in Denmark is likely to have contributed to the reported increase in stage I disease by increasing awareness in both the medical community and in the general population, resulting in increased skin self-examination, more physician consultations, and earlier detection.…”
Section: Discussionmentioning
confidence: 98%
“…As earlier diagnosis is the principal factor that can improve the prognosis of patients with melanoma (6), there is considerable interest in the development of screening programs. The SCREEN project in northern Germany suggested that population screening may have a substantial impact on melanoma incidence and 5-year mortality (7,8) leading to the implementation of a national statutory skin cancer early detection program in Germany in 2008. However, such mass screening is not currently recommended by the U.S. Preventive Services Task Force (9) or in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence effects of the SCREEN project were analyzed and compared to Saarland, a federal state of Germany where no population-based screening took place. The incidence of MM increased during the SCREEN period and decreased when screening activities stopped in Schleswig-Holstein, while no such changes in incidence were seen in Saarland [31]. A rise in incidence during the SCREEN period has also been observed for BCC and SCC in Schleswig-Holstein, but not in Saarland [32].…”
Section: Steps Towards a Standardized And Systematic Skin Cancer Scrementioning
confidence: 61%